A morphometric analysis of hominin teeth attributed to Australopithecus, Paranthropus and Homo - Susan J. Dykes (South African Journal of Science, 2016)
Teeth are the most common element in the fossil record and play a critical role in taxonomic assessments. Variability in extant hominoid species is commonly used as a basis to gauge expected ranges of variability in fossil hominin species. In this study, variability in lower first molars is visualised in morphospace for four extant hominoid species and seven fossil hominin species. A size-versus-shape-based principle component analysis plot was used to recognise spatial patterns applicable to sexual dimorphism in extant species for comparison with fossil hominin species. In three African great ape species, variability occurs predominantly according to size (rather than shape), with the gorilla sample further separating into a male and a female group according to size. A different pattern is apparent for the modern human sample, in which shape variability is more evident. There is overlap between male and female modern humans and some evidence of grouping by linguistic/tribal populations. When fossil hominin species are analysed using equivalent axes of variance, the specimens group around species holotypes in quite similar patterns to those of the extant African great apes, but six individual fossil molars fall well outside of polygons circumscribing holotype clusters; at least three of these specimens are of interest for discussion in the context of sexual dimorphism, species variability and current species classifications. An implication of this study is that, especially in the case of modern humans, great caution needs to be exercised in using extant species as analogues for assessing variability considered to be a result of sexual dimorphism in fossil hominin species.